Long-term water types and satellite chlorophyll a variability in a river discharge environment around Ieodo Ocean Research Station - Kyung-Ae Park; Na-Yeon Cha; Kwang-Young Jeong; Do-Seong Byun; Byoung-Ju Choi; Joon-Soo Lee (Scientific Reports)
Abstract A monthly climatology of long-term optical water types in the East China Sea (ECS), covering the region around the Ieodo Ocean Research Station (I-ORS) and the Yangtze River discharge (YZRD) area, was constructed using two decades of satellite MODIS reflectance data. SMAP salinity data revealed the gradual seasonal dispersion of low-salinity water from the YZR mouth toward I-ORS, particularly intensifying in summer. Despite the influx of riverine water over I-ORS, satellite-based optical water type analysis indicated that I-ORS area maintained its clearest water types during summer—a novel finding. Cross-wavelet analysis between long-term YZRD and Chl-a concentrations at I-ORS displayed intermittent insignificant correlations without sustained patterns. Spatial distribution of phase-lag regression results between the Chl-a and YZRD revealed non-direct routes as northeastward spreading from the river mouth and a counterclockwise dispersion path south of I-ORS. This pattern aligned with riverine particle-tracking experiments following surface currents, underscoring the role of currents in transporting nutrients from the river, which is crucial for Chl-a blooms in the summer oligotrophic environment. Our results highlight the influence of riverine discharge on ECS marine conditions, emphasizing the role of physical and biological interactions in shaping Chl-a distributions within marine ecosystems in summer oligotrophic environment.